PELAKSANAAN REWARD DAN PUNISHMENT - Meyzi Heriyanto, Jon Rizal, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2020)
Reward and Punishment Implementation. The background of this research by In an organization or company, a program of rewards and sanctions is urgently needed, because this program is one of the important parts of the company's many work programs. This study aims to describe the implementation of reward and punishment and the factors that influence the implementation of rewards and punishments for employees of the Human Resources Development and Human Resources Agency in Batang Hari Regency. This study uses a qualitative descriptive research method approach. Primary data was obtained directly through interviews from key informants, namely the Head of the BKPSDM Batang Hari Regency, 2 (two) Heads of Fields, and 2 (two) Employees of the BKPSDMD in Batang Hari Regency. The results of the study indicate that the implementation of rewards and punishments at the BKPSDM office in Batang Hari Regency has generally been carried out as applicable regulations.